Intestinal Carcinoid Tumours in a Father and Daughter - Tuya Pal; Alexander Liede; Margot Mitchell; Alain Calender; Steven A Narod (Canadian Journal of Gastroenterology)
Familial cases of carcinoid tumours that are not associated with any known syndrome or disease are extremely rare. All cases reported in the world literature have involved carcinoid tumours of the gastrointestinal tract. Two cases of carcinoid tumours of the small intestine in a father and daughter are presented. Laboratory analyses did not support the hypothesis that the occurrence of carcinoid tumours in this family is a variant of the multiple endocrine neoplasia type 1 syndrome. A review of the literature on familial occurrence of intestinal carcinoid tumours in the absence of any other known carcinoid tumour-predisposing genetic syndrome is provided.